68.9k views
19 votes
Simplify and then evaluate the equation

when a = 2 and b = 4.
b2 + 3(b-b2) – 2a = [?]
Help please

2 Answers

5 votes

Answer:

8

Explanation:

4(2)+3(b-4(2))-2(2)=8

User Hasan Kucuk
by
4.9k points
9 votes

9514 1404 393

Answer:

-24

Explanation:

We can simplify this to ...

b^2 +3(b -b^2) -2a

= b^2 +3b -3b^2 -2a

= -2b^2 +3b -2a . . . . . . . simplified form

This can be made easier for evaluation by factoring out b.

= (-2b +3)b -2a

Using the given values, this is

= (-2(4) +3)(4) -2(2)

= (-5)(4) -4

= -24 . . . . value of the expression

Simplify and then evaluate the equation when a = 2 and b = 4. b2 + 3(b-b2) – 2a = [?] Help-example-1
User Keshav Aditya R P
by
5.2k points